The Clinical Value of Lipid Abnormalities in Early Stage Cervical Cancer - Jiang Q; Wang L; Jin M; Shou Y; Zhu H; Li A (International Journal of General Medicine, 2022)
Qi Jiang,1 Luhui Wang,1 Mengya Jin,1 Yueyao Shou,1 Haiyan Zhu,1,2,* Anyang Li1,* 1Department of Gynecology, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325027, People’s Republic of China; 2Department of Gynecology, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, Shanghai, 200126, People’s Republic of China*These authors contributed equally to this workCorrespondence: Anyang Li, Department of Gynecology, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325027, People’s Republic of China, Tel +86 19817583796, Email Anyang846856005@vip.126.com Haiyan Zhu, Department of Gynecology, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, 2699 Gaoke West Road, Shanghai, 200126, People’s Republic of China, Tel +86 57755069162, Email zhuhaiyandoc@sina.comBackground: To describe the characteristics of plasma lipid proliferation in cervical cancer and further evaluate the prognostic significance of lipid levels in cervical cancer.Methods: We retrospectively reviewed 1713 patients with cervical cancer in our hospital. The preoperative plasma lipid profile, including cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL), and low-density lipoprotein cholesterol (LDL), of 1713 cervical cancer patients was compared with that of 10,397 healthy women. Then, we evaluated the impact of lipids on overall survival (OS) and recurrence-free survival (RFS) in cervical cancer using univariate and multivariate Cox models.Results: While plasma TC, TG, and LDL were significantly higher, HDL was lower in patients with cervical cancer than in healthy women. TG was identified as an independent predictor for RFS and OS among patients with cervical cancer. Further stratified by age, patients with higher TGs showed a significantly worse RFS and OS than those with lower TGs among patients ≥ 50 years old but not among those < 50 years old.Conclusion: Cervical cancer was associated with a disordered lipid profile. Hypertriglyceridemia was an independent poor prognostic indicator for cervical cancer, especially for elderly patients. Strengthening lipid management may be beneficial for improving postoperative OS and RFS in patients with cervical cancer.Keywords: cervical cancer, lipid profile, triglyceride, cholesterol, prognosis